Поєднання соціального й асоціального капіталу як критерій посттрансформаційного стану економіки - Архієреєв, Сергій Ігоревич (Інститут економіки та прогнозування Національної академії наук України, 2014)
The article introduces the notion of antisocial capital and shows its interrelation to the definition of social capital. The author proposes and analyzes the coefficients of the propagation of social and antisocial capital. The article shows that an institutional criterion of the post-transformational condition of the economy may be the combination of social and antisocial capital. A conclusion is made on the preservation of the post-transformational condition of the market institutional environment in the postsocialist economies until the present time.
Combination of social and antisocial capital as a criterion of the post-transformational condition of the economy
Keywords: соціальний капітал; асоціальний капітал; довіра; посттрансформаційна економіка; social capital; antisocial capital; trust; post-transformational economy